The Impact of Lobbying on the Allocation of Political Authority - Sonia Falconieri (Tinbergen Institute, 2001)
This paper studies the internal organizational design of politicalinstitutions in presence of lobbying. We consider a legislature ascomposed of two bodies: the floor and an informational committee. Thefloor has the (formal) power to choose the policy to be implemented.The policy outcome is ex ante unknown but the committee has anexpertise to learn the payoff pattern of the feasible policies.In this context, we investigate the impact of lobbying on the optimalallocation of political authority ( agenda control) between the floorand the standing committee.The allocation of the agenda control is here described as the choicebetween two alternative legislative rules: open versus closed rule.We show that, in presence of lobbying, the effectiveness of a closedrule as an incentive device towards the committee is noticeablyreduced while the costs imposed to the floor are higher. As aconsequence, we find that a closed rule is never an optimal choicefor the floor.
Keywords: D70; D72; D80; 330; Lobbying; Procedure Rule; Open/Closed Rule; Interessenpolitik; Neue politische Ökonomie; Theorie; Politische Entscheidung